Standardizing terminology for text recycling in research writing. Issue 3 (2nd February 2021) - Moskovitz, Cary
Abstract: Because research in science, engineering and medical fields advances incrementally, researchers routinely write papers that build directly on their prior work. While each new research article is expected to make a novel contribution, researchers often need to repeat some material—method details, background and so on—from their previous articles, a practice called 'text recycling'. While increasing awareness of text recycling has led to the proliferation of policies, journal editorials and scholarly articles addressing the practice, these documents tend to employ inconsistent terminology—using different terms to name the same key ideas and, even more problematic, using the same terms with different meanings. These inconsistencies make it difficult for readers to know precisely how the ideas or expectations articulated in one document relate to those of others. This paper first clarifies the problems with current terminology, showing how key terms are used inconsistently across publisher policies for authors, guidelines for editors and textbooks on research ethics. It then offers a new taxonomy of text‐recycling practices with terms designed to align with the acceptability of these practices in common research writing and publishing contexts.